Sexual Dimorphism in Mandibular Canine Crown Dimensions in Early Adolescents: A Hospital based Study - Kanak Priya1, Poonam Agrawal2, Dinesh Kumar Bagga3, Hiten Kalra4, Disha Sirohi5, Ritika Gupta5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Determination of sex is valuable in forensic investigations. Forensic odontology plays a major role due to the hardness and chemical stability of teeth. This study was done to find out the utility of mandibular canine crown dimensions as a tool for sex determination in North Indian population. Crown length and mesiodistal width of right and left mandibular canines were measured on the 60 casts and analyzed to assess sex difference using Students ‘t’ test. The canine crown parameters as measured for males and females when compared were found to be statistically significant. However, when these parameters were compared between left and right sides for the same sex, they were found to be statistically insignificant.